Marketing educativo para fidelizar aspirantes a la carrera de marketing en la ULVR - Bermúdez Salvador, Jorge Javier (2023)
Educational Marketing to retain applicants for the Marketing career at the ULVR is a research topic that is based on studying the reasons why applicants for the marketing career fail to complete their study process. You want to know the reasons or real factors, based on a widely detailed market study. The research topic is related to strategic business development because through educational marketing, strategies will be planned, which will help achieve specific objectives in the short and long term, along with the creation of ideas that contribute to the environment, since being a career that focuses on constant innovation and problem solving, has the necessary ability to want to make people aware of many factors that exist today worldwide.